If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 2 = a + 4 Reorder the terms: 2 + 2a = a + 4 Reorder the terms: 2 + 2a = 4 + a Solving 2 + 2a = 4 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 2 + 2a + -1a = 4 + a + -1a Combine like terms: 2a + -1a = 1a 2 + 1a = 4 + a + -1a Combine like terms: a + -1a = 0 2 + 1a = 4 + 0 2 + 1a = 4 Add '-2' to each side of the equation. 2 + -2 + 1a = 4 + -2 Combine like terms: 2 + -2 = 0 0 + 1a = 4 + -2 1a = 4 + -2 Combine like terms: 4 + -2 = 2 1a = 2 Divide each side by '1'. a = 2 Simplifying a = 2
| 79-(101-5y)=2(101-5y)+y | | 6.5(x-4)=-0.5x+30 | | 5=(x+8) | | -5x+6y=30 | | 19x=12x | | 11x+2=5x+10+58 | | -5-x=1+2x | | 4d=7-7 | | 8x+2+70+60= | | -5(a-6)+2a=9 | | (3x-6y-1)+(-x+y+10)= | | 3w+10=-3+8w-9w | | 4(2y+1)-2y=-26 | | 1/3(102-12c)=5(3c+10) | | 5x-x-3=2x+6 | | M-3=7m-21 | | 4n-(7-6n)=13 | | 6x+3=3(2x+3) | | 2x-11=23 | | 3x=52 | | (9x-8y-11)-(5x-9y+1)= | | -8=1.3x+x | | 10=-2.3(4x+5) | | 18b-21=15b+3 | | 7x-[-5]=-9 | | 4=2.3x+9-1.3x | | 6m=2m-8 | | 2x(28)=x+4 | | 26x+24=-39x-6 | | -6x-9x+11= | | 3.4(x+2)=-1 | | 2x-28=x+4 |